Persepsi Pustakawan Perpustakaan Umum terhadap Transformasi Perpustakaan Berbasis Inklusi Sosial - Niswa Nabila Sri Bintang Alam; Rusdan Kamil (Perpustakaan Nasional, 2021)
The National Library of Indonesia launched a social inclusion-based library transformation program based on the library for all movement in collaboration with the Ministry of National Development Planning / BAPPENAS. In 2019, all libraries participating in this program totaled 359 public libraries spread across all provinces in Indonesia. The purpose of this study was to determine the perceptions of general librarians in Indonesia towards social inclusion-based library programs that have been implemented for the last two years. Two previous studies related to librarian perception research and the development of social transformation programs are the basis for the development of this research. The population in this study was 2477 librarians who work in public library institutions in Indonesia from various levels ranging from central to the village, while the determination of the research sample was carried out by simple random sampling technique with a confidence level of 94.5% and a margin of error of 5.7% so that 273 respondents were obtained. The research results are expected to provide input on national strategies and policies for the implementation of a social inclusion-based library transformation program.